Advanced bond coat material for tbc with improved thermal cycle fatigue resistance and sulphidation resistance
By using a nickel-based adhesive coating material to form a dense α-alumina layer, the delamination problem of thermal barrier coatings under high temperature and sulfur presence is solved, achieving significant resistance to thermal cycling fatigue and sulfurization, and extending thermal cycling life.
Patent Information
- Application Number
- CN201980092919.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-03-07
- Publication Date
- 2026-01-27
- Estimated Expiration
- 2039-03-07
AI Technical Summary
Existing thermal barrier coating systems are prone to delamination under high temperatures and in the presence of sulfur, leading to reduced thermal cycling fatigue and shortened lifespan, and thus failing to meet the high-temperature operation requirements of modern gas turbine engines.
A nickel-based adhesive coating material containing specific components, including chromium, tantalum, molybdenum, aluminum, silicon, yttrium, and carbon, is used to form a dense α-alumina layer to block oxygen diffusion, reduce thermal stress, and improve bonding strength.
It significantly improves the thermal barrier coating's resistance to thermal cycling fatigue and sulfidation, extending its thermal cycle life, especially exhibiting more than twice the furnace cycle life at high temperatures.
Smart Images

Figure CN113423852B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to advanced binder coating materials for thermal barrier coatings (TBCs) that exhibit improved resistance to thermal cycling fatigue and sulfidation. The advanced binder coating material may be in the form of a powder, alloy, binder coat, or coating, and may be used in conjunction with a topcoat material as a thermally sprayed powder to obtain a thermal barrier coating (TBC) system. The invention also relates to methods for reducing delamination of the topcoat from a substrate (e.g., a gas turbine engine component). Background Technology
[0002] A complete thermal barrier coating system comprises a topcoat (e.g., a thermal barrier coating (TBC)) and a binder coating or adhesive layer. A typical binder coating is made of an MCrAlY alloy, where M represents Ni, Co, Fe, or a combination thereof. To improve the performance of the binder coating, Hf, Re, and Pt, along with various other rare earth elements, are often added to advanced binder coatings. A typical topcoat is made of one or more stabilized zirconium oxide (ZrO2) selected from yttrium oxide, ytterbium oxide, cerium oxide, titanium oxide, magnesium oxide, calcium oxide, lanthanum oxide, or dysprosium oxide, or from gadolinium zirconate (Gd2Zr2O7).
[0003] A thermal cycling fatigue resistance (TBC) system is applied and bonded to a substrate (e.g., a superalloy), and this TBC system protects the substrate in hot and harsh environments (e.g., in a gas turbine engine environment). An adhesive coating or bonding layer is placed between the topcoat and the substrate, bonding the topcoat to the substrate. The adhesive coating or bonding layer is formed from an adhesive coating material, which may be in powder form for application to the substrate. The adhesive coating or bonding layer formed from the adhesive coating material affects the thermal cycling fatigue resistance and sulfurization resistance of the topcoat (e.g., the TBC), the effectiveness of which can be evaluated by the furnace cycle life of the TBC in the presence and absence of sulfur. The TBC can degrade due to high temperatures and harsh environments (e.g., the presence of sulfur). For example, using oil with a high sulfur content as fuel in an industrial gas turbine with a TBC is a significant factor in reducing the TBC life.
[0004] A significant failure of a complete thermally charged composite (TBC) system occurs at the bond / topcoat interface. When a TBC system is exposed to high temperatures, an oxide layer called thermally grown oxide (TGO) nucleates and grows between the bond and topcoat layers to block further inward diffusion of oxygen and prevent substrate oxidation. A dense α-alumina layer of TGO is desirable because it effectively blocks oxygen diffusion and also grows slowly itself. However, there are significant differences in the coefficients of thermal expansion among the topcoat, bond, and TGO. When a TBC system undergoes thermal cycling (from room temperature to operating temperature to room temperature), significant internal stresses caused by temperature changes accumulate at the topcoat / TGO interface and the TGO / bond interface. As the TGO layer thickens, these thermal internal stresses become increasingly high, eventually leading to delamination of the topcoat (e.g., the TBC) due to thermal stress. Modern jet engines and industrial gas turbines are seeking higher operating temperatures to improve performance and energy efficiency, thus requiring higher thermal shock resistance from TBC systems.
[0005] As disclosed in U.S. Patent No. 4,124,737 to Wolfra et al., a variety of coatings can be used to protect metallic alloy substrates from wear or corrosion in many environments. These coatings range from pure metallic coatings to pure ceramic coatings and include cermet-type coatings with a high volume fraction of ceramic phase in the metallic matrix. As disclosed by Wolfra, one of the most challenging environments for providing protection to metallic substrates is one that combines high-temperature oxidation or sulfidation corrosion with fretting wear or impact-induced wear. According to Wolfra et al., only a few coatings are successful in this type of environment, and practically none are successful when temperatures exceed approximately 1800°F. In relatively low temperature ranges, i.e., up to 1000°F or 1200°F, cermet coatings with tungsten carbide binders are typically and very successfully used. However, above these temperatures, this type of coating oxidizes too quickly to be used for any extended time period. Cermets, as a large class, also suffer from a lack of fatigue resistance and impact resistance. Wolfa et al. disclosed coating compositions, corrosion- and abrasion-resistant coated articles, and methods for producing such articles, wherein the coated articles consist of a substrate having a coating layer composed of a cobalt-based alloy containing 17-35% chromium, 5-20% tantalum, 0-2% yttrium, 0-2.5% silicon, 0-3.0% manganese, 0.5-3.5% carbon, 0-5% or 14% aluminum (all by weight percentage), and 0-50% by volume of at least one metal oxide. The Wolfa compositions are not adhesive coatings but rather overcoatings (without a topcoat) designed to improve abrasion and corrosion resistance at high temperatures.
[0006] U.S. Patent No. 4,117,179 to Jackson et al. discloses an article with improved high-temperature oxidation and corrosion resistance, comprising: (a) a superalloy substrate containing a carbide-reinforcing phase, and (b) a coating composed of chromium, aluminum, carbon, at least one element selected from iron, cobalt, or nickel, and optionally an element selected from yttrium or rare earth elements. Another embodiment comprises an aluminized outer coating of the superalloy. According to Jackson, the carbon content of the coating must be sufficient to completely saturate all MCrAlY phases with carbon; however, insufficient to form excessive carbides within the coating composition, which has a detrimental effect on the oxidation and corrosion resistance of the coating under superalloy service conditions.
[0007] U.S. Patent No. 5,141,821, granted to Lugscheider, discloses a corrosion-resistant and wear-resistant high-temperature composite material based on an MCrAlY type alloy as the matrix metal, wherein platinum and / or rhodium are alloying elements in an amount of 5-15% by weight, and comprising particles of mechanically resistant substances in the form of carbides and / or mixtures of elements vanadium, niobium, tantalum, titanium, zirconium, hafnium, chromium, molybdenum and / or tungsten, which are included in the matrix metal in an amount of 0.01-75% by weight, preferably 5-75% by weight, based on the high-temperature composite material.
[0008] U.S. Patent No. 4,275,124 to McCas et al. discloses wear-resistant, oxidation-resistant, and corrosion-resistant coating alloys and coated superalloy articles useful at temperatures up to 1000°C or higher, comprising chromium, aluminum, yttrium, and carbon, with the balance selected from nickel, cobalt, iron, or mixtures thereof. According to McCas et al., the coating obtained by the present invention consists essentially of a carbon-rich MCrAlY matrix containing fine metal carbides on the order of 1-2 micrometers and chromium carbides on the order of 12 micrometers. Embodiments require a coating composition, by weight, consisting essentially of 18-80% chromium, 1.2-29% aluminum, up to 4.8% yttrium, and 0.6-11% carbon, with the balance selected from nickel, cobalt, and iron, or mixtures thereof. According to US Patent No. 4,124,737 of McCas et al. and Wolfa et al., a Co-Cr alloy coating containing tantalum carbide for wear resistance at high temperatures is disclosed, which is essentially composed of 17-35 wt% Cr, 5-20 wt% Ta, 0.5-3.5 wt% C, with the balance being Co. Other embodiments contain rare earth metals, Al, Si, and various metal oxides. Regarding the use of tantalum (Ta), McCas et al. agree with Wolfa et al. that Ta is a solid solution reinforcing agent in high-temperature alloys. However, according to McCas et al., although it is superior to W and Mo in terms of resistance to oxidation corrosion, as a refractory metal, Ta can at most not improve the oxidation corrosion resistance of CoCrAlY alloys, and it is most likely to degrade them if other elements in the system are simply replaced.
[0009] This invention provides an advanced adhesive coating for use as a topcoat (e.g., thermal barrier coating (TBC)) in high-temperature gas turbine engine components. In the high-temperature environment of gas turbine engine components, with and without sulfur, TBCs bonded to a substrate (e.g., superalloy) using an adhesive coating exhibit unexpectedly high resistance to thermal cycling fatigue and sulfidation, as well as unexpectedly extended thermal cycle life. The complete TBC system forms a desired, dense α-alumina layer of TGO at the interface between the adhesive coating and the topcoat (e.g., TBC), sufficient to block further inward diffusion of oxygen to prevent substrate oxidation. The formed TGO is not so thick as to cause delamination failure due to thermal stress, achieving an unexpectedly extended time. Summary of the Invention
[0010] According to the present invention, a bonding coating material that provides unexpectedly high resistance to thermal cycling fatigue and sulfidation, as well as unexpectedly extended thermal cycling life, in the high-temperature environment of gas turbine engine components in the presence and absence of sulfur, comprises:
[0011] a) Chromium, in an amount of 10% to 30% by weight, preferably 20% to 26% by weight.
[0012] b) At least one of tantalum and molybdenum, wherein the total amount of tantalum and molybdenum is from 3% to 15% by weight, preferably from 5% to 12% by weight, more preferably from 9% to 11% by weight.
[0013] c) Aluminum, in an amount of 5% to 13% by weight, preferably 6% to 10% by weight.
[0014] d) Silicon, in an amount of 0.1% to 1.4% by weight, preferably 0.3% to 1.1% by weight, more preferably 0.5% to 1.0% by weight.
[0015] e) Yttrium, in an amount of 0.1% to 0.8% by weight, preferably 0.3% to 0.75% by weight.
[0016] f) Carbon, in an amount of 0% to 1.2% by weight, preferably 0.3% to 1.1% by weight, more preferably 0.5% to 1.0% by weight.
[0017] g) Dysprosium, in an amount of 0% to 1% by weight, for example 0.1% to 0.5% by weight.
[0018] h) Cerium, in an amount of 0% to 1% by weight, for example 0.1% to 0.5% by weight, and
[0019] i) The balance is nickel, and the percentages from a) to i) add up to 100 by weight.
[0020] The total amount of at least one of tantalum and molybdenum, as well as the amounts of aluminum and silicon, are each critical for preventing the top coating from delaminating from the bonding coating or the coating itself, and for achieving unexpectedly high thermal cycling fatigue resistance and sulfurization resistance, as well as unexpectedly long thermal cycling life, in the presence or absence of sulfur, under high-temperature environments (e.g., gas turbine engine components).
[0021] In various aspects of the invention, the adhesive coating material may be in powder form, may be an alloy, or may be an adhesive coating or a coating layer. The alloy may be in powder form, or in the form of wires, rods, or bars, or may be an adhesive coating or a coating layer. In each case, the chemical composition may be as described for the adhesive coating material.
[0022] In another aspect of the invention, the thermal spray powder may include a separate binder coating material or a binder coating material together with a topcoat material, such as at least one of a thermal barrier coating (TBC) material or an abrasion-resistant coating material.
[0023] In another aspect of the invention, a thermal barrier coating (TBC) system includes a top coat and a bond coat or bond coating, wherein the top coat is bonded to the bond coat or bond coating. The coated substrate comprises a substrate and a TBC system bonded to the substrate via the bond coat or bond coating. The TBC system may be produced from the thermal spray powder. The TBC system is bonded to the substrate (e.g., a superalloy) via the bond coat or bond coating between the top coat and the substrate. The complete TBC system forms a desired, slowly growing, dense layer of thermally grown oxide (TGO) at the interface between the bond coat and the top coat (e.g., TBC), sufficient to block further inward diffusion of oxygen to prevent substrate oxidation. The formed TGO is not so thick as to cause delamination due to thermal stress, resulting in a surprisingly extended time period.
[0024] In another aspect of the invention, delamination of the topcoat from the substrate is reduced by bonding the topcoat to the substrate with an adhesive coating or coating (e.g., the alloy of the invention), and nucleating and growing a thermally grown oxide (TGO) between the topcoat and the adhesive coating to block further inward diffusion of oxygen and prevent substrate oxidation. The topcoat may comprise a thermal barrier coating (TBC), and the substrate may comprise a gas turbine engine component. The TGO may comprise α-alumina and reduce delamination due to thermal internal stress, with or without sulfur. Brief description of the attached diagram
[0026] The invention is further illustrated by the accompanying drawings, in which:
[0027] Figure 1 A substrate with a thermal barrier coating (TBC) system is illustrated schematically, the system including a top coating, such as a thermal barrier coating (TBC) bonded to an adhesive coating or coating according to the invention.
[0028] Figure 2 This is an illustrative description of what happens after subjecting the vehicle to the high temperatures and harsh environments found in gas turbine engines. Figure 1 The coated substrate forms a desired dense layer of thermally grown oxide (TGO) at the interface between the adhesive coating and the top coating (e.g., TBC), which, according to the invention, is sufficient to block further inward diffusion of oxygen to prevent substrate oxidation. Detailed Implementation
[0029] This invention provides advanced adhesive coating materials for forming adhesive coatings or bonding coatings that bond a topcoat (e.g., a thermal barrier coating (TBC)) to a substrate (e.g., a superalloy used in high-temperature gas turbine engine components). In the high-temperature environment of gas turbine engine components, with and without sulfur, TBCs bonded to a substrate (e.g., a superalloy) using adhesive coatings exhibit unexpectedly high resistance to thermal cycling fatigue and sulfidation, as well as unexpectedly extended thermal cycling life. The complete TBC system forms a desired dense α-alumina layer of TGO at the interface between the adhesive coating and the topcoat (e.g., the TBC), which is sufficient to block further inward diffusion of oxygen to prevent substrate oxidation. The formed TGO is not so thick as to cause delamination failure due to thermal stress, achieving an unexpectedly extended time period.
[0030] The binder coating material is nickel-based and includes at least one of chromium and, critically, a total amount of tantalum and molybdenum, as well as a critical amount of aluminum, to prevent the topcoat from delaminating from the binder coating or the coating itself, and to achieve unexpectedly high thermal cycling fatigue resistance and sulfurization resistance, as well as unexpectedly long thermal cycling life, in high-temperature environments (e.g., gas turbine engine components) with and without sulfur. Expensive materials such as cobalt, rhenium, hafnium, and platinum are not required in the binder coating material or the binder coating itself. Furthermore, according to the National Institute for Occupational Safety and Health (NIOSH), occupational exposure to cobalt can damage the eyes, skin, heart, and lungs, and may cause cancer. Reducing the use of cobalt in powder form is consistent with global environmental and health policies and regulations.
[0031] Compared to the furnace cycle life of cobalt-based binder coatings (e.g., CoNiCrAlY binder coatings, such as Diamalloy® 4700), the furnace cycle life of top coatings (e.g., thermal barrier coatings (TBCs)) using the nickel-based binder coating materials of this invention can be unexpectedly two or even three times longer. The TBC system of this invention exhibits unexpectedly excellent stability at temperatures above 1800°F (e.g., above 2000°F) with and without sulfur.
[0032] For example, in a furnace cycle test (FCT) without sulfur, with a 70-minute cycle time (heating from room temperature to an operating temperature of 1135°C (2075°F) within 10 minutes and holding for 50 minutes, followed by cooling to room temperature within 10 minutes), the mean failure cycles of a TBC system with a cobalt-based Diamalloy 4700 binder coating or coating can be used as a baseline. In embodiments of the invention, TBC systems with the Ni-based binder coating or coating of the present invention provide unexpectedly higher mean failure cycles compared to the baseline Diamalloy 4700 binder coating lifetime, wherein the cycle lifetime is increased by at least 75%, for example at least 125%, or even at least 200%, as demonstrated in the appended examples. In embodiments of the invention, unexpectedly longer cycle life was also achieved using the Ni-based adhesive coating or coating of the invention at test temperatures of 1150°C (2102℉) or even higher, wherein the cycle life was increased by at least 55%, for example at least 80%, or even at least 150%, compared to the baseline Diamalloy 4700 adhesive coating life, as demonstrated in the appended examples.
[0033] In the presence of sulfur, in a furnace cycle test (FCT) with a 60-minute cycle time (heating from room temperature to an operating temperature of 1121°C (2050°F) within 10 minutes and holding for 40 minutes, followed by cooling to room temperature within 10 minutes), the mean failure cycles of a TBC system with a cobalt-based Diamalloy 4700 binder coating or coating can be reduced by approximately 33% in the presence of sulfur (compared to the absence of sulfur). However, in embodiments of the invention, TBC systems with the Ni-based binder coating or coating of the present invention provide unexpectedly higher mean failure cycles in the presence of sulfur, compared to the baseline Diamalloy 4700 binder coating lifetime in the absence of sulfur, with a cycle lifetime increase of at least 65%, for example, at least 100%, as demonstrated in the appended examples. Moreover, in embodiments of the invention, the Ni-based binder coating or coating of the present invention achieves substantially the same unexpectedly high mean failure cycle count as obtained in the absence of sulfur, and the increase in lifetime in the presence of sulfur, as demonstrated in the appended examples.
[0034] According to the present invention, a bonding coating material that provides unexpectedly high resistance to thermal cycling fatigue and sulfidation, as well as unexpectedly extended thermal cycling life, in the high-temperature environment of gas turbine engine components in the presence and absence of sulfur, comprises:
[0035] a) Chromium, in an amount of 10% to 30% by weight, preferably 20% to 26% by weight.
[0036] b) At least one of tantalum and molybdenum, wherein the total amount of tantalum and molybdenum is from 3% to 15% by weight, preferably from 5% to 12% by weight, more preferably from 9% to 11% by weight, for example...
[0037] 1) 5% to 15% by weight of Mo, without any Ta, or
[0038] 2) 3 to 7 wt% Mo, having 3 to 7 wt% Ta, or,
[0039] 3) 5% to 15% Ta by weight, without any Mo.
[0040] c) Aluminum, in an amount of 5% to 13% by weight, preferably 6% to 10% by weight.
[0041] d) Silicon, in an amount of 0.1% to 1.4% by weight, for example 0.5% to 1.4% by weight, preferably 0.3% to 1.1% by weight, more preferably 0.5% to 1.0% by weight.
[0042] e) Yttrium, in an amount of 0.1% to 0.8% by weight, for example 0.3% to 0.8% by weight, preferably 0.3% to 0.75% by weight.
[0043] f) Carbon, in an amount of 0% to 1.2% by weight, for example 0.5% to 1.2% by weight, preferably 0.3% to 1.1% by weight, more preferably 0.5% to 1.0% by weight.
[0044] g) Dysprosium, in an amount of 0% to 1% by weight, for example 0.1% to 0.5% by weight.
[0045] h) Cerium, in an amount of 0% to 1% by weight, for example 0.1% to 0.5% by weight, and
[0046] i) The balance is nickel, and the percentages from a) to i) add up to 100 by weight.
[0047] In embodiments of the present invention, both tantalum and molybdenum may be present in the adhesive coating material, or only one of tantalum or molybdenum may be present while the other is absent, provided that:
[0048] 1) The total amount of tantalum and molybdenum is 3% to 15% by weight.
[0049] 2) Preferably 5% to 12% by weight
[0050] 3) More preferably 9% to 11% by weight.
[0051] For example, in embodiments of the present invention, for the adhesive coating or adhesive coating material:
[0052] 1) The amount of tantalum may be from 0% to 12% by weight, and the amount of molybdenum may be from 0% to 12% by weight, but the total amount of tantalum and molybdenum must be from 3% to 15% by weight.
[0053] 2) When molybdenum is not used (molybdenum content is 0%) or when molybdenum is used, the tantalum content can be from 4% by weight to 11% by weight. However, in the latter case, if molybdenum is used, the amount of molybdenum can be up to 4% by weight when the tantalum content is at the upper limit of 11% by weight, so that the total amount of tantalum and molybdenum is 15% by weight.
[0054] 3) When tantalum is used or not used, the amount of molybdenum can be from 4% by weight to 11% by weight. However, in the latter case, if tantalum is used, the amount of tantalum can be up to 4% by weight when the molybdenum content is at the upper limit of 11% by weight, so that the total amount of tantalum and molybdenum is 15% by weight. In a preferred embodiment, tantalum may or may not be used with molybdenum.
[0055] In embodiments of the invention, the adhesive coating material can be manufactured in powder or bulk form (e.g., wire, rod, bar, or plate). The adhesive coating material powder can be a homogeneous mixture of individual powders of each component of the adhesive coating material. The adhesive coating material powder can also consist of particles, each particle containing all or some of the components of the adhesive coating material. For example, an alloy of all the components of the adhesive coating material can be ground to obtain a powder. The particle size of the adhesive coating material can depend on the coating method employed. Conventional particle size distributions typically used for a given coating method can be used in the adhesive coating material of the present invention.
[0056] In other embodiments, the adhesive coating material may be an alloy, or when applied and bonded to a substrate, the adhesive coating material may be an adhesive coating or layer on the substrate. The alloy may be in powder form, or in the form of wire, rod, bar, or plate, or when applied and bonded to a substrate, it may be an adhesive coating or layer. In each case, the chemical composition of the alloy, in each of its forms, or when applied and bonded to the substrate as an adhesive coating or layer on the substrate, may be as described for the adhesive coating material. As used herein, an alloy is as conventionally defined and is a mixture of chemical elements that forms an impure substance (mixture) that retains metallic properties. The difference between an alloy and an impure metal is that, with an alloy, the added elements are well controlled to produce the desired properties, while impure metals (e.g., wrought iron) are less controlled but are generally considered useful. Alloys are made by mixing two or more elements, at least one of which is a metal. This is often referred to as the host metal or base metal, and the name of that metal may also be the name of the alloy. Other components may be metallic or may not be metallic, such as carbon, but they will be soluble and dissolve into the mixture when mixed with the molten base. As used herein, an alloy may be a solid solution of a metal and at least one other element, typically another metal that forms a single crystalline phase. An alloy may be a combination of metals, or a combination of one or more metals with one or more other elements. An alloy may be defined by its metallic binding properties, and may be a solid solution (single phase) of metallic elements or a mixture of metallic phases (two or more solutions).
[0057] In another aspect of the invention, the thermal spray powder may include a separate binder coating material or a binder coating material together with a topcoat material, such as at least one of a thermal barrier coating (TBC) material, a wear-resistant metal, a wear-resistant alloy, or a wear-resistant ceramic.
[0058] The topcoat material can be any conventional or known topcoat material or thermal barrier coating (TBC) material, such as those used for coating gas turbine engine components, as disclosed in U.S. Patent Application Publication No. 2018-0099909, the disclosure of which is incorporated herein by reference in its entirety. Other non-limiting examples of topcoat materials that may be used include aluminum alloys (e.g., AlSi) (typically with a particle size of 30-150 μm) currently used in commercially available wear-resistant materials, nickel alloys (e.g., NiCrFe, NiCrAl, NiCrAlY, and NiCoCrAlY) and cobalt alloys (e.g., CoNiCrAlY) (using a typical particle size of 5-100 μm) currently used in commercially available wear-resistant materials. Topcoat materials may also include zirconia-based ceramics (e.g., dysprosium oxide-stabilized ZrO2 and yttrium oxide-stabilized ZrO2) (typically with a particle size of 10-150 μm) and iron-based alloys (e.g., FeCrAl and FeCrAlY) (typically with a particle size of 5-100 μm) currently used in commercially available wear-resistant materials and TBCs. Topcoat materials may include conventional or known fibers or fibrous materials for controlling the porosity of the topcoat material, as disclosed in PCT International Publication No. WO2018152328, the disclosure of which is expressly incorporated herein by reference in its entirety.
[0059] Other known thermal barrier coatings (including those with vertical cracks) can also be used as topcoats. Numerous publications and patents disclose thermal barrier coatings with vertical cracks, such as U.S. Patent No. 5,073,433 to Taylor and U.S. Patent No. 8,197,950 to Taylor et al., which disclose segmented coatings. The disclosure of each of these U.S. patents is incorporated herein by reference in its entirety.
[0060] The substrate can be any known or conventional material or article requiring a topcoat or barrier coating (TBC). Non-limiting examples of substrates include alloys or superalloys used in the manufacture of gas turbine engine components, such as Hastelloy® X disclosed in U.S. Patent No. 4,124,737 to Wolfa et al., the disclosure of which is incorporated herein by reference in its entirety. As disclosed by Wolfa et al., Hastelloy® X has the following nominal composition: 22.0 wt% chromium, 9.0 wt% molybdenum, 18.5 wt% iron, 1.5 wt% cobalt, 0.6 wt% tungsten, 1.0 wt% silicon, 1.0 wt% manganese, 0.1 wt% carbon, and the balance nickel. Other non-limiting examples of known and conventional substrates that can be coated with the adhesive coating or adhesive coating of the present invention include steel, stainless steel, other iron-based alloys with low alloy content, chromium and chromium-based alloys, and refractory metals and refractory metal-based alloys. Non-limiting examples of superalloy substrates to which the adhesive coating or coating of the present invention can be applied are known carbide-reinforced superalloys, such as nickel-based and cobalt-based superalloys, directionally solidified nickel-based and cobalt-based superalloys (including eutectic alloys), and refractory alloys, as disclosed in U.S. Patent No. 4,117,179, the disclosure of which is incorporated herein by reference in its entirety. Non-limiting examples of substrates or articles to which the adhesive coating or coating of the present invention can be applied include turbine blades and impellers in gas turbine engines.
[0061] In another aspect of the invention, as in Figure 1 As illustrated schematically, a thermal barrier coating (TBC) system 1 includes a top coating 2 and an adhesive coating or adhesive coating 3, wherein the top coating 2 (e.g., TBC) is bonded to the adhesive coating or adhesive coating 3 at a top coating / adhesive coating interface 5. A coated substrate 10 includes a substrate 15 and the thermal barrier coating system 1 bonded to the substrate 15 by the adhesive coating or adhesive coating 3 at a substrate / adhesive coating interface 20. The thermal barrier coating system 1 can be produced by thermal spraying powder. The thermal barrier coating system 1 is bonded to the substrate 15 (e.g., a superalloy or gas turbine component) by the adhesive coating or adhesive coating 3 between the top coating 2 and the substrate 15.
[0062] As in Figure 2 As illustrated in the diagram, after being subjected to the high temperatures and harsh environments, such as those found in gas turbine engines, Figure 1The complete TBC system 1 of the coated substrate 10 forms a desired slow-growing dense α-aluminum oxide layer of thermally grown oxide (TGO) 25 at the interface 5 between the bond coat 3 and the top coat 2 (e.g., TBC), which is sufficient to block further inward diffusion of oxygen to prevent oxidation of the substrate 15. The formed TGO 25 is not so thick as to cause failure due to delamination of the top coat 2 from the bond coat or the bond coat 3 and the substrate 15 due to thermal internal stress, achieving an unexpectedly extended period of time. In an embodiment of the present invention, the thickness X of the TGO can range from submicron to 12 microns, or 0 < X < 12 μm, preferably 0 < X < 10 μm.
[0063] In an embodiment of the present invention, multiple bond coats or bond coats 3 and multiple top coats 2 can be used, where each top coat 2 is located on top of the bond coat 3 in an alternating manner to provide multiple TBC systems 1, which are stacked and bonded one above the other, and the bottommost bond coat 3 is bonded to the substrate 15.
[0064] In a further aspect of the present invention, a method for reducing delamination of the top coat from the substrate is provided, which bonds the top coat to the substrate with a bond coat or coating (e.g., the alloy of the present invention), and nucleates and grows thermally grown oxide (TGO) between the top coat and the bond coat to block further inward diffusion of oxygen to prevent oxidation of the substrate. The top coat can comprise a thermal barrier coating (TBC), and the substrate can comprise a gas turbine engine component. The TGO can comprise α-aluminum oxide and reduce delamination due to thermal internal stress in the presence or absence of sulfur.
[0065] Conventional thermal spraying methods (such as air plasma spraying, suspension plasma, high velocity oxygen fuel spraying (HVOF), low pressure plasma spraying (LPPS), vacuum plasma spraying (VPS), chemical vapor deposition (CVD), plasma physical vapor deposition (PS-PVD), physical vapor deposition (PVD) (which includes vacuum deposition methods such as sputtering and evaporation)) and conventional flame spraying methods (such as combustion wire spraying and combustion powder spraying, arc wire spraying, powder flame spraying and electron beam physical vapor deposition (EBPVD)) can be used to deposit, apply or laminate the bond coat or bond coats or bond layer and the top coat (e.g., TBC) on the substrate. Conventional and known coating thicknesses can be used for the bond coat or coating and the top coat or TBC.
[0066] The present invention is further illustrated by the following non-limiting examples, where all parts, percentages, ratios and proportions are by weight, all temperatures are in °C, and all pressures are at atmospheric pressure, unless otherwise specified. Examples
[0067] The compositions of the three nickel-based alloy samples of the present invention and the comparative or baseline cobalt-based alloy sample Diamalloy® 4700 (adhesive coating material) used to manufacture the adhesive coating for the substrate to be coated are shown in Table 1. The materials listed in Table 1 were sprayed onto the Hastelloy X substrate by a high-speed oxy-fuel spraying method (HVOF method) to form four different adhesive coatings. As disclosed by Wolfa et al., Hastelloy® X has the following nominal composition: 22.0 wt% chromium, 9.0 wt% molybdenum, 18.5 wt% iron, 1.5 wt% cobalt, 0.6 wt% tungsten, 1.0 wt% silicon, 1.0 wt% manganese, 0.1 wt% carbon, and the balance nickel. Then, the same top coating (TBC) of 7% by weight of Y2O3 partially stabilized ZrO2 (Amdry® 204NS-1 manufactured by Oerlikon Metco) was air plasma sprayed onto the binder coating to form four different TBC systems, named Comparative TBC-D4700, TBC Example 1, TBC Example 2 and TBC Example 3.
[0068] For each synthesized TBC, a full TBC system performance classification using an FCT (furnace cycle test) emphasizing the bond coating / topcoat interface was performed, with a cycle time of 70 minutes (heating from room temperature to 1135°C in 10 minutes, holding at 1135°C for 50 minutes, and cooling to room temperature in 10 minutes). The FCT was also performed at 1150°C instead of 1135°C. The results are shown in Table 2.
[0069] TBCs can deteriorate due to harsh environments, and the presence of sulfur in the TBC (i.e., using oil with a high sulfur content as fuel for industrial gas turbines) is a significant factor reducing TBC life. To evaluate the effect of sulfur, a concentration of 40 mg / cm³ was used. 2 Na₂SO₄ salt powder was placed on the surface of the comparative D4700 TBC and the surface of the TBC Example 3 of the present invention. The samples were then heated from room temperature to 920°C (the melting point of Na₂SO₄ is about 880°C) and held at this temperature for 24 hours to allow the molten salt to permeate into the TBC system. The salted and unsalted samples (also exposed to 920°C for 24 hours before the FCT test) were then subjected to the FCT test, with a cycle time of 60 minutes (heated from room temperature to 1121°C in 10 minutes, held at 1121°C for 40 minutes, and cooled to room temperature in 10 minutes), and the results are shown in Table 3.
[0070] Table 1 shows the composition of the tested samples, Table 2 shows the results of the furnace cycle test (FCT) for the unsalted samples, and Table 3 shows the results of the furnace cycle test (FCT) for the salinized samples.
[0071] Table 1: Composition of adhesive coating materials (alloys) used to manufacture adhesive coatings for substrates to be coated.
[0072] sample Co Ni Cr Mo Ta Al Si Y C Compared to baseline TBC D4700 margin 31.51 20.6 -- -- 7.73 -- 0.42 0.012 TBC 1 -- margin 10-30 5-15 -- 5-13 0.5-1.4 0.3-0.8 0.5-1.2 TBC 2 -- margin 10-30 3-7 3-7 5-13 0.5-1.4 0.3-0.8 0.5-1.2 TBC 3 -- margin 10-30 -- 5-15 5-13 0.5-1.4 0.3-0.8 0.5-1.2
[0073] Table 2: Furnace Cycle Test (FCT) Results of Adhesive Coating Materials (Alloys) Used for Manufacturing Adhesive Coatings for Coated Substrates (70 minutes, 1135°C and 1150°C)
[0074] sample Increase in cycle life, in percentage, tested at 1135°C Increase in cycle life, in percentage, tested at 1150°C Compared to baseline TBC D4700 n / a n / a TBC 1 80% 59% TBC 2 134% 83% TBC 3 207% + (Test stopped) 158% + (Test stopped)
[0075] Table 3: Sulfurization resistance (60 minutes, 1121°C) of adhesive coating materials (alloys) used to manufacture adhesive coatings for substrates to be coated.
[0076]
[0077] *All data in Table 3 are for comparison with the unsalted baseline TBC 4700 sample.
[0078] The data listed in Table 2 show that, compared to the TBC lifetime of the baseline alloy Diamalloy® 4700 (TBC D4700) commonly used in the thermal barrier coating industry, the alloy of the present invention unexpectedly increases the TBC lifetime by 80% to over 207% at a test temperature of 1135°C, as measured by the increase in the percentage of mean failure cycles. The data listed in Table 2 also show that, compared to the TBC lifetime of the baseline alloy Diamalloy® 4700, the alloy of the present invention unexpectedly increases the TBC lifetime by 59% to over 158% at a test temperature of 1150°C, as measured by the increase in the percentage of mean failure cycles.
[0079] The results in Table 3 indicate that the TBC lifetime of the salted baseline alloy TBC (TBC D4700) was reduced by 33% compared to the TBC lifetime of the unsalted sample (302.5 cycles). The results in Table 3 also show that the salted alloy TBC-1 of the present invention has a surprisingly longer lifetime, exceeding that of the unsalted baseline TBC D4700 by 68%. The results in Table 3 further show that the salted alloy TBC-2 of the present invention has a surprisingly longer lifetime, exceeding that of the unsalted baseline TBC D4700 by at least 107.6% (at the stop point). Additionally, the results in Table 3 show that the salted alloy TBC-3 of the present invention has a surprisingly longer lifetime, exceeding that of the salted baseline TBC D4700 by at least 101.6% (at the stop point). Similarly, as shown in Table 3, the TBC-3 samples of the present invention had unexpectedly similar lifetimes at the stop point, whether salted or unsalted, and also unexpectedly had a lifetime at least 101.6% longer than the baseline alloy TBC D4700 in comparison unsalted.
[0080] Furthermore, at least because the invention is disclosed herein in a manner that enables people to make and use the invention, for example, due to the disclosure of specific exemplary embodiments, the invention may be practiced without any steps, additional elements or additional structures not specifically disclosed herein, for example for simplicity or efficiency.
[0081] Note that the foregoing embodiments are provided for illustrative purposes only and are in no way intended to limit the invention. Although the invention has been described with reference to exemplary embodiments, it should be understood that the terms used herein are descriptive and illustrative, not restrictive. Changes may be made within the scope of the appended claims, as described and modified herein, without departing from the scope and spirit of the invention in its various aspects. Although the invention has been described herein with reference to specific devices, materials, and embodiments, the invention is not intended to be limited to the details disclosed herein; rather, the invention extends to all functionally equivalent structures, methods, and uses, for example, within the scope of the appended claims.
Claims
1. An adhesive coating material, comprising: a) Chromium, in an amount of 10% to 30% by weight. b) At least one of tantalum and molybdenum, wherein: 1) 5% to 12% molybdenum, or 2) 3% to 7% molybdenum and 3% to 7% tantalum, The total amount of tantalum and molybdenum is 5% to 12% by weight. c) Aluminum, in an amount of 6% to 10% by weight. d) Silicon, in an amount of 0.3% to 1.1% by weight. e) Yttrium, in an amount of 0.1% to 0.8% by weight. f) Carbon, in an amount of 0.3% to 1.1% by weight. g) Dysprosium, in an amount of 0% to 1% by weight. h) Cerium, in an amount of 0% to 1% by weight, and i) The balance is nickel. The percentages from a) to i) add up to 100 weight.
2. The adhesive coating material as described in claim 1, wherein the material is selected from powder, alloy, wire, rod, bar, plate and adhesive coating.
3. A thermal spray powder comprising the adhesive coating material as described in claim 1.
4. The thermal spray powder as described in claim 3, further comprising at least one of a thermal barrier coating (TBC) material, a wear-resistant metal, a wear-resistant alloy, or a wear-resistant ceramic.
5. The adhesive coating material as described in claim 1, wherein: a) The amount of chromium is 20% to 26% by weight.
6. An alloy comprising: a) Chromium, in an amount of 10% to 30% by weight. b) At least one of tantalum and molybdenum, wherein: 1) 5% to 12% molybdenum, or 2) 3% to 7% molybdenum and 3% to 7% tantalum, The total amount of tantalum and molybdenum is 5% to 12% by weight. c) Aluminum, in an amount of 6% to 10% by weight. d) Silicon, in an amount of 0.3% to 1.1% by weight. e) Yttrium, in an amount of 0.1% to 0.8% by weight. f) Carbon, in an amount of 0.3% to 1.1% by weight. g) Dysprosium, in an amount of 0% to 1% by weight. h) Cerium, in an amount of 0% to 1% by weight, and i) The balance is nickel. The percentages from a) to i) add up to 100 weight.
7. The alloy of claim 6, wherein: a) The amount of chromium is 20% to 26% by weight.
8. An adhesive coating comprising the alloy of claim 6.
9. A thermal barrier coating system comprising a top coating and a bonding coating as claimed in claim 8.
10. A coated substrate comprising a substrate and a thermal barrier coating system of claim 9 bonded to the substrate by the adhesive coating.
11. A method for reducing delamination of a topcoat from a substrate, comprising bonding the topcoat to the substrate using the alloy of claim 6 as an adhesive coating, and nucleating and growing a thermally grown oxide (TGO) between the topcoat and the adhesive coating to block further inward diffusion of oxygen to prevent oxidation of the substrate.
12. The method of claim 11, wherein the top coating comprises a thermal barrier coating (TBC), the substrate comprises a gas turbine engine component, and the TGO comprises α-alumina and reduces delamination due to thermal internal stress in the presence of sulfur.
13. A method for reducing delamination of a topcoat from a substrate, comprising bonding the topcoat to the substrate using the adhesive coating material of claim 1 as an adhesive coating, and nucleating and growing a thermally grown oxide (TGO) between the topcoat and the adhesive coating to block further inward diffusion of oxygen to prevent oxidation of the substrate.
14. The method of claim 13, wherein the top coating comprises a thermal barrier coating (TBC), the substrate comprises a gas turbine engine component, and the TGO comprises α-alumina and reduces delamination due to thermal internal stress in the presence of sulfur.
Citation Information
Patent Citations
Ceramic material for high temperature service
US20180099909A1
Oxidation corrosion resistant superalloys and coatings
US4117179A
High temperature wear resistant coating composition
US4124737A
Carbon bearing MCrAlY coating
US4275124A
Thermal barrier coating for substrates and process for producing it
US5073433A
